LEARNING BASED ON SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) THROUGH WHATSAPP APPLICATION IN THE TIME OF THE COVID-19 PANDEMIC - Nur Halimah; Nurul Anam; Naily Inayatul Maghfirah; Zainal Arifin (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTThe Covid-19 pandemic has caused early childhood education institutions to experience various problems. Learning that has been carried out face-to-face, must eventually be replaced with online learning using digital technology intermediaries. All early childhood education institutions have difficulty dealing with this reality, so that the development of early childhood abilities cannot be developed optimally. One institution that was able to deal with this reality well is RA Nurud Dholam, Mumbulsari Village, Mumbulsari District. This institution was able to deal with it by using the STEM approach through the Whatsapp application media. From this background, this research was focused on describing the implementation of STEM-loaded learning through the Whatsapp application in group B RA Nurud Dholam, Mumbulsari Village, Mumbulsari District, Jember Regency. The research method used was a qualitative approach and the type of qualitative descriptive research. The results of this study indicate that STEM-based learning through the Whatsapp application at RA Nurud Dholam Mumbulsari Village during the covid-19 pandemic went well, because this learning can stimulate children's intelligence, improve children's mathematical and naturalistic logical abilities and make learning more effective and efficient.Keywords: STEM-Based Learning, Whatsapp Application, Covid-19 Pandemic